Analisis Peran Taman Pendidikan Al-Qur'an dalam Membentuk Akhlak Anak Usia Dini di Indonesia - Mia Anggita Putri; Ayu Alawiyah; Nirmala Ade Revitri; Pita Andri Yani; Rika Sulastri; Haikal Haikal; M. Zainal Arifin (Bulletin of Indonesian Islamic Studies, 2022)
The cultivation of good character, or Akhlāqul Karīmah, needs to begin at an early age since childhood is crucial for character development. However, in Purwosari Village, Lampung, Indonesia, many children still show a lack of respect for their parents, teachers, and peers. This study aims to assess the role of TPA Al-Ikhlas in promoting moral values among early childhood learners. The research employs a qualitative approach, gathering data through observations, interviews, and document analysis. The data were analyzed in three stages: data reduction, data presentation, and conclusion drawing. To ensure validity, triangulation techniques were used. The results indicate that TPA Al-Ikhlas plays a positive role in shaping children's morals through the teaching of the Qur'an, prayer procedures, and moral lessons. Methods of instruction include lectures, habituation, modeling behavior, and supervision. Factors supporting this effort include parental and community support, while challenges arise from the unrestricted use of electronic media and negative social influences.